Hospitalization Among Medicare-Reimbursed Skilled Home Health Recipients - O’Connor, Melissa (Home Health Care Manag Pract, 2012)
This article presents a summary and critique of the published empirical evidence between the years 2002 and 2011 regarding rehospitalization among Medicare-reimbursed, skilled home health recipients. The knowledge gained will be applied to a discussion regarding ACH among geriatric home health recipients and areas for future research. The referenced literature in MEDLINE, PubMed and Cochrane databases was searched using combinations of the following search terms: home care and home health and Medicare combined with acute care hospitalization, rehospitalization, hospitalization, and adverse events and limited to studies conducted in the United States. Twenty-five research studies published in the last eight years investigated hospitalization among patients receiving Medicare-reimbursed, skilled home health. Empirical findings indicate telehomecare can reduce hospitalizations and emergency room use. The identification of risk factors for hospitalization relate to an elder’s sociodemographic, clinical and functional status that can be identified upon admission and interventions taken in order to reduce hospitalizations. Disease management, frontloading nurse visits, the structure of home health services and OBQI are also among the interventions identified to reduce hospitalizations. However, the body of evidence is limited by a paucity of research and the over reliance on small sample sizes. Few published studies have explored methods that effectively reduce hospitalization among Medicare-reimbursed skilled home health recipients. Further research is needed to clarify the most effective ways to structure home health services to maximize benefits and reduce hospitalization among this chronically ill geriatric population.